Respuesta :
Answer:
46
Step-by-step explanation:
First, start off by substituting the values of a, b, and c, into the equation.
We know a = 5, b = 3, and c = -1, so now substitute.
6a + 2b - 6c + 4
6(5) + 2(3) - 6(-1) + 4
Now that we've substituted the values, we can solve the equation.
6(5) + 2(3) - 6(-1) + 4
30 + 6 + 6 + 4
= 46
So, the answer is 46.
I hope this helps! ôヮô
Answer:
46
Step-by-step explanation:
All you need to do is subsitute the variable with what it says the number is.
Let's first start out with 6a from the equation. We know that a= 5, so that means it wants you to multiply 6 by 5, which is 30.
Now let's do 2b. It says b= 3, so do 2 times 3. It equals 6.
So far we have 30+6-6c+4
Let's do -6c. We know that c= -1, so let's multiply -1 and -6. Negative and negative equals positive. And 6 times 1 is 6. So the outcome is positive 6.
We got 30+6+6+4
Solve.
30+6= 36
36+6= 42
And 42+4= 46. :)